2011
DOI: 10.1177/0032885511404380
|View full text |Cite
|
Sign up to set email alerts
|

Inmate Custody Levels and Prison Rule Violations

Abstract: Researchers have recently combined individual-level data with institutional measures to detect prison-level correlates of inmate misconduct. Although this body of literature has yielded insights into how the prison environment contributes to misconduct, we argue that it has ignored an important level of analysis, namely the custody level. As some inmates are placed in more restrictive confinement than others, custody levels may absorb some of the variation in individual-level and/or prison-level correlates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 73 publications
(95 reference statements)
4
50
0
1
Order By: Relevance
“…In a study conducted by Worrall & Morris (2011), a positive relationship between prison misconduct and custody level was found with higher custody levels being associated with a greater likelihood of misconduct. Berk & de Leeuw (1999) also found an association between inmate's security classification score and inmate misconduct in California prisons.…”
Section: Institutional Culturementioning
confidence: 97%
“…In a study conducted by Worrall & Morris (2011), a positive relationship between prison misconduct and custody level was found with higher custody levels being associated with a greater likelihood of misconduct. Berk & de Leeuw (1999) also found an association between inmate's security classification score and inmate misconduct in California prisons.…”
Section: Institutional Culturementioning
confidence: 97%
“…Other research indicates disciplinary infractions are influenced by the overall characteristics of the inmates as well as the staff (Camp et al, 2003). Although earlier work has shown custody levels have a minimal impact on misconduct (Camp & Gaes, 2005), a more recent study of Texas prisoners by Worrall and Morris (2011) found that increases in custody levels (i.e., higher levels of risk) were associated with a greater likelihood of rule violations.…”
Section: Prior Research On Prison Misconductmentioning
confidence: 99%
“…Prison crowding has been linked with inmate violence (e.g., Franklin et al, 2006;), as has sentence length (e.g., Camp et al, 2003;Craddock, 1996;Jiang & Fisher-Giorlando, 2002). Inmates' custody level, perhaps more indicative of "deprivation" than any other variable, has also been linked with violence, although not in a clear manner (Bench & Allen, 2003;Berecochea & Gibbs, 1991;Worrall & Morris, 2011).…”
Section: Deprivationmentioning
confidence: 99%
“…Another study found that as much as one in four young inmates were victimized within just one month (O'Donnell & Edgar, 1998). More recent data revealed that 14 percent of inmates acted violently toward other inmates within a five-year period (Worrall & Morris, 2011). Regardless of the data source, it is clear that "a significant proportion of prisoners are subjected to multiple forms of victimization" (Maitland & Sluder, 1998:64; see also Bottoms, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation